Application of Inverted Index Technique to Improve Document Search Effectiveness in Office Administration System - Septa, Septa; Dirmansyah, Dirmansyah; S, Fithria Rizka; Tu, Le Minh (Journal of Office Administration : Education and Practice, 2024)
This research aims to explain in depth the use of the inverted index technique in the information retrieval process. Inverted index is a crucial data structure in modern search systems, allowing quick and efficient access to relevant documents or information. This research falls into the category of descriptive qualitative research and uses data collection methods through a thorough literature study. The results show that systems that implement indexing methods, especially inverted index, can significantly improve the performance of search results. This technique plays an important role in improving the completeness and relevance of documents desired by users. With inverted index, the system can quickly identify and return documents that best match the user's query, improving the accuracy and efficiency of the search process.